EXPERIMENTAL STUDY OF THERMAL EFFECT OF DRYING, HEATING, BLOWING MACHINE WITH DIFFERENT STAGE - Singh, Aditya Pratap; Sahni, Disha Dinesh; Dubey, Arpit (International Journal of Research -GRANTHAALAYAH, 2016)
Drying is the oldest method of preserving food. The early American settlers dried foods such as corn, apple slices, currants, grapes, and meat. Compared with other methods, drying is quite simple. In fact, you may already have most of the equipment on hand. Dried foods keep well because the moisture content is so low that spoilage organisms cannot grow. Drying will never replace canning and freezing because these methods do a better job of retaining the taste, appearance, and nutritive value of fresh food. But drying is an excellent way to preserve foods that can add variety to meals and provide delicious, nutritious snacks. One of the biggest advantages of dried foods is that they take much less storage space than canned or frozen foods.